(NsOSREDOTO^ENNYE NELINEJNYE WOLNY (B/s - (NmOLOTKOW(B, (NiWAN aNATOLXEWI^s; (NwAKULENKO(B, (NsERGEJ aWGUSTOWI^s; (NlENINGRADSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Na(B.(Na(B. (NvDANOWAs ((NlENINGRAD (B:s (NiZD(B-(NWO lgu(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 232-238 (161 (NNAZW(B.)s
Keywords: (NwOLNY NELINEJNYEs